2016
DOI: 10.3390/ijms17020197
|View full text |Cite
|
Sign up to set email alerts
|

Apobec-1 Complementation Factor (A1CF) Inhibits Epithelial-Mesenchymal Transition and Migration of Normal Rat Kidney Proximal Tubular Epithelial Cells

Abstract: Apobec-1 complementation factor (A1CF) is a member of the heterogeneous nuclear ribonucleoproteins (hnRNP) family, which participates in site-specific posttranscriptional RNA editing of apolipoprotein B (apoB) transcript. The posttranscriptional editing of apoB mRNA by A1CF in the small intestine is required for lipid absorption. Apart from the intestine, A1CF mRNA is also reported to be highly expressed in the kidneys. However, it is remained unknown about the functions of A1CF in the kidneys. The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Similar results were observed using an MTT assay (Figure S2I-L), which is an alternative method to EdU for measuring cell proliferation. FCM data indicated that overexpression of A1CF decreased apoptosis (Figures S1B,F and S2A,E), whereas A1CF knockdown increased apoptosis (Figure S2C,D,G,H) of OSRC-2 and 786-O cells, which is consistent with the reported results in other tumor cells [17,18] or kidney epithelial cells [13].…”
Section: A1cf Promotes the Proliferation Of Renal Cancer Cells And De...supporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were observed using an MTT assay (Figure S2I-L), which is an alternative method to EdU for measuring cell proliferation. FCM data indicated that overexpression of A1CF decreased apoptosis (Figures S1B,F and S2A,E), whereas A1CF knockdown increased apoptosis (Figure S2C,D,G,H) of OSRC-2 and 786-O cells, which is consistent with the reported results in other tumor cells [17,18] or kidney epithelial cells [13].…”
Section: A1cf Promotes the Proliferation Of Renal Cancer Cells And De...supporting
confidence: 90%
“…More recently, another Sox2-cre-driven global deletion of A1cf in mice did not result in embryonic lethality because they bypassed the implantation stage [10]. In addition to the liver and small intestine, A1CF is highly expressed in the kidney [1,10,11] and has been genetically [12] and molecularly [13] associated with kidney function. Further phenotypic analysis indicates that A1CF loss results in water homeostasis defects and increases protein and solute concentrations in the kidney [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is in contrast to Apobec1 knockout mice, which display decreased HDL (Nakamuta et al 1996). A1CF has been reported by multiple groups to be highly expressed in the kidney (Lellek et al 2000;Dur et al 2004) and has been genetically (Pattaro et al 2016) and molecularly (Huang et al 2016) associated with kidney function. Given this, we evaluated whether our A1CF-null model displayed any kidney-related defects.…”
Section: A1cf Has Novel Physiological Rolesmentioning
confidence: 82%
“…Apobec-1 complementation factor (A1CF) belongs to heterogeneous nuclear ribonucleoproteins (hnRNP) family and is highly conserved across species. 5,6 It contains three non-identical RNA recognition motifs (RRM) and a unique C-terminal auxiliary domain. 7 A1CF participates in the post-transcriptional cytidine (C) to uridine (U) RNA editing of apolipoprotein-B (ApoB) messenger RNA (mRNA) by co-acting with APOBEC1.…”
Section: Introductionmentioning
confidence: 99%